The Effect Of Quantum Reading Strategy On The Intensive Reading Ability Of 4th Grade Students Of State-Owned Elementary School No.10 Bandar Buat Padang - Siti Nur, Azlin; Sukma, Elfia; Astimar, Nelly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this study is to find out the effect of quantum reading strategy on the intensive reading ability of 4th-grade students of state-owned Elementary School No.10 Bandar Buat, Padang. This study used a quantitative approach in the form of a quasi-experimental design. The research design of this study is the non-equivalent posttest-only control group design and the sampling technique is saturation sampling. Based on the analysis results of the hypothesis test with the significance level of 5%, it was found that tcalculation > ttable (2,95995 > 1,67155). It is concluded that the quantum reading strategy has a significant effect on the intensive reading ability of 4th-grade students at state-owned Elementary School No.10 Bandar Buat, Padang.Keywords: quantum reading, intensive reading, elementary school students